Materialism and happiness as predictors of willingness to buy counterfeit luxury brands - Trinh, Viet Dung (Curtin University, 2014)
The study examines the effect of material values – namely material success, material happiness, material essentiality and material distinctiveness – and life satisfaction and lawfulness with regards to consumers’ attitude toward counterfeit luxury brands and their affect on consumers’ willingness to buy counterfeit luxury brands. To test the research model, a new scale to measure and conceptualize materialism was developed and two new constructs: “material essentiality” and “material distinctiveness” were created.